Molecularly Imprinted Polymers (MIPs) as Theranostic Systems for Sunitinib Controlled Release and Self-Monitoring in Cancer Therapy - Ortensia Ilaria Parisi; Mariarosa Ruffo; Rocco Malivindi; Anna Francesca Vattimo; Vincenzo Pezzi; Francesco Puoci (MDPI AG, 2020)
Cytotoxic agents that are used conventionally in cancer therapy present limitations that affect their efficacy and safety profile, leading to serious adverse effects. In the aim to overcome these drawbacks, different approaches have been investigated and, among them, theranostics is attracting interest. This new field of medicine combines diagnosis with targeted therapy; therefore, the aim of this study was the preparation and characterization of Molecularly Imprinted Polymers (MIPs) selective for the anticancer drug Sunitinib (SUT) for the development of a novel theranostic system that is able to integrate the drug controlled release ability of MIPs with Rhodamine 6G as a fluorescent marker. MIPs were synthesized by precipitation polymerization and then functionalized with Rhodamine 6G by radical grafting. The obtained polymeric particles were characterized in terms of particles size and distribution, ξ-potential and fluorescent, and hydrophilic properties. Moreover, adsorption isotherms and kinetics and in vitro release properties were also investigated. The obtained binding data confirmed the selective recognition properties of MIP, revealing that SUT adsorption better fitted the Langmuir model, while the adsorption process followed the pseudo-first order kinetic model. Finally, the in vitro release studies highlighted the SUT controlled release behavior of MIP, which was well fitted with the Ritger-Peppas kinetic model. Therefore, the synthesized fluorescent MIP represents a promising material for the development of a theranostic platform for Sunitinib controlled release and self-monitoring in cancer therapy.